THE ZAKAT INDEX MEASUREMENT SUPPORTING THE ZAKAT COMMUNITY DEVELOPMENT PROGRAM IN SUMOBITO VILLAGE - Rico Wardana Putra; Eko Fajar Cahyono (Universitas Airlangga, 2020)
This research has a purpose of knowing priority status at Sumobito Village of Jombang Regency in receiving zakat from BAZNAS through the Zakat Community Development (ZCD) program by using Index Desa Zakat (IDZ). This research uses mixed method. The qualitative method uses literature, observation and interview study whereas the quantitative method uses the IDZ score with Multi-stage Weight Index calculation. Secondary and primary data use the kind of data. Primary data is given from the result of structural interviews, questionnaire and observation. Where secondary data is given from journal articles, books, BPS, etc. The result of this research finds that the IDZ score is 0.59 at Sumobito village by index range score is lied in 0.41-0.60. It means that the prosperity level at Sumobito village is in good condition and it can be a consideration to receive zakat and donation.Keyword: Index Desa Zakat (IDZ), Zakat Community Development (ZCD), BAZNAS, SumobitoREFFERENCE Kementrian Agama Republik Indonesia. (2014). Al-Quran dan terjemahnya. Bandung: Sygma Creative Media Corp. [BAZNAS] Badan Amil Zakat. (2017). Zakat Community Development.Beik, IS, Arsyianti LD. (2016). Measuring zakat impact on poverty and welfare using CIBEST Model. Journal of Islamic Monetary Economics and Finance, 1(2), 141-160.[BPS] Badan Pusat Statistik Kota Jombang. (2017).[BPS] Badan Pusat Statistik Desa Sumobito. (2017).Hadi Yasin, Ahmad. (2012). Panduan zakat praktis. Jakarta: Dompet Dhuafa Republika.Hafidhuddin, D. (2002). Zakat dalam perekonomian modern. Jakarta: Gema InsaniHafidhuddin D, Nasar MF, Kustiawan T, Beik IS, Hakiem. (2015). Fiqih zakat Indonesia.Jakarta: Gema Insani.Herdayanti, Novi. (2018). Pengukuran Indeks Desa Zakat dalam mendukung program Zakat Community Development (Studi kasus: Desa Popongan Kabupaten Semarang). Skripsi tidak diterbitkan. Bogor: Institut Pertanian Bogor.Jamil, Alfan. (2019). Implementasi Indeks Desa Zakat pada Desa Sungai Dua Kecamatan Rambutan (untuk desa yang terukur dan berkemajuan). Skripsi tidak diterbitkan. Palembang: UIN Raden Fatah Palembang.Kementerian Desa. (2015). Pembangunan daerah tertinggal dan transmigrasi. Jakarta: Kementerian Desa.Kementerian Perencanaan Pembangunan Nasional/ Badan Perencanaan Pembagunan Nasional dan Badan Pusat Statistik. (2014). Indeks Pembanguan Desa: Tantangan pemenuhan standar pelayanan minimum desa. Jakarta: Bappenas.Kensiwi. (2019). Identifikasi Indeks Desa Zakat di Kampung Sejahtera Kelurahan Sumberjaya Kota Bengkulu. Skripsi tidak diterbitkan. Institut Agama Islam Negeri Bengkulu.Mintarti, N. (2011). Pemberdayaan masyarakat berbasis zakat: Model-model dan pengukuran kinerja program. Executive Development Training Center. Bogor: Institut Pertanian Bogor.Profile Desa Sumobito Kabupaten Jombang. 2019Puskas BAZNAS. 2017. indeks Desa Zakat. Jakarta: BAZNAS.Puskas BAZNAS. (2019). Dampak zakat melalui program balai ternak di Kabupaten Tanah Datar. Jakarta: BAZNAS.Puskas BAZNAS. (2019). Dampak zakat terhadap tingkat kesejahteraan mustahik: Studi kasus lembaga-lembaga program zakat. Jakarta: BAZNAS.Rencana Pembangunan Jangka Menengah Desa (RPJM) Desa Sumobito 2014-2018. Jakarta: Bappenas.Rencana Pembangunan Jangka Menengah Nasional (RPJM 2015-2019). Jakarta: Bappenas.Undang-Undang No 23 Tahun 2011 tentang Pengelolaan zakat.Undang-Undang No 6 Tahun 2014 tentang DesaUtami, Siti Halida. (2014). Pengaruh Zakat Produktif terhadap Pemberdayaan Mustahik di Kota Medan. Jurnal Ekonomi dan Keuangan, 2(6), 353-366.